Perbandingan Struktural dan Doktrinal Perbuatan Melawan Hukum di Indonesia dan Filipina: Kajian Komparatif Hukum Perdata Berdasarkan Pasal 1365 Kitab Undang-Undang Hukum Perdata dan Article 2176 Philippine Civil Code - Jordan Baros Indraputra Silalahi; Thomas Rifera Indraputra Silalahi; Jemimah Puteri Rajagukguk; Veronica Enjelina Manalu; Elizabeth Prima Ratrisari; Velliana Tanaya (Dinasti Review Publisher, 2026)
This study comparesnon-contractual civil liability, namely tort (PMH) as recognized in Indonesia based on Article 1365 of the Civil Code and Quasi-Delictin the Philippines based on Article 2176 of the Civil Code of the Philippines, whichoriginated from different legal systems, namely the Civil Law System and the HybridLaw System applied in the Philippines. The objectives of this study are toidentify differences in concepts, analyze the handling ofintentional torts, and evaluate theimpact of jurisprudence on compensation. The method applied in this study is a normative juridical method using aconceptual and comparative systemic approach, analyzing primary data (legislation) and secondary data (in the form of doctrines and decisions). The results of the studyshow that Indonesian PMH is extensive, covering violations ofsocial propriety, while Philippine Quasi-Delict is restrictive,requiring “absence of contract”. Indonesia deals with intentional actssubstantively, coveringboth fault and negligence, while the Philippines uses procedural instruments where the element of intent is still recognizedas stipulated in Article 2177. That Stare decisisin the Philippines creates superior legal certainty, in contrast to Indonesia, whichrelies on judicial discretion (ex aequo et bono), which has the potential tocause variability in judgments Kajian ini mengkomparasi antara pertanggungjawaban perdata non-kontraktual yaitu Perbuatan Melawan Hukum (PMH) yang dikenal di Indonesia dengan dasar hukum Pasal 1365 KUHPerdata dan Quasi-Delict Philipine dengan dasar hukum Pasal 2176 Civil Code of The Philipine yang berasal dari sistem hukum berbeda yaitu Civil Law System dengan Hybrid Law System yang diterapkan di Filipina. Tujuan dari kajian ini ialah mengidentifikasi diferensiasi dalam konsep, menganalisis penanganan perbuatan yang dilakukan dengan sengaja (intentional torts) serta mengevaluasi dampak dari yurisprudensi terhadap ganti rugi. Metode yang diterapkan dalam penelitian ini adalah metode yuridis normatif dengan menggunaan pendekatan konseptual dan komparatif sistemik, menganalisis data primer (peraturan perundang-undangan) dan data sekunder (berupa doktrin dan putusan). Hasil penelitian menunjukkan: bahwa PMH Indonesia bersifat ekstensif, mencakup pelanggaran kepatutan sosial, sementara Quasi-Delict Filipina bersifat restriktif, mensyaratkan